Solid state fermentation of agricultural waste by indigenous aspergillus versicolor a6 for pectinase production used in bioretting of pepper - Frazer, anak Midot (Universiti Malaysia Sarawak (UNIMAS), 2012)
pectinases are important enzymes that are widely used in various industries. In this study, application of enzymatic retting using pectinase enzyme preparation for the production of white pepper (Piper nigrum L.) was conducted. Pectinolytic fungi have been successfully isolated from agricultural soil, decaying fruits and water retted pepper berries samples. High potency index for pectinase was obtained from isolate A6 and FP 13 with value of 3.309±0.131 and 3.133±0.115, respectively. Both isolates were then subsequently selected for further developmej Molecular identification using internal transcribed spacer primers identified both selected fungi as Aspergillus versicolor. Investigation was conducted to select suitable fermentation system for pectinase production using the A. versicolor isolates. The results showed a statistically significant difference where higher pectinase enzyme activity was obtained in solid state fermentation as compared to submerged fermentation for both A. versicolor isolates. In the experiments, isolate A6 showed higher pectinase activity on the basis of exo-polygalacturonase activity and protein concentration as compared to isolate FP13. The use of agricultural waste such as banana peels and pepper wastes as substrate for pectinase production was also assessed. The isolate A6 produced higher pectinolytic enzyme activity when banana peels was used as carbon source. Banana peels were also found to contain higher amount of pectin and deemed as suitable for the fungal growth as well as inducing pectinase production. Sugarcane bagasse was only used as solid support for fermentation. Fermentation parameters for pectinase production by A. versicolor A6 in a gram scale solid state fermentation with banana peels and sugarcane bagasse were at incubation temperature of 30°C with initial media pH of pH 5.5 and MnS04 of 0.02% (w/v). Enzyme characterization studies were also conducted using the crude pectinase enzyme produced. It was shown that the enzyme produced had a higher affinity towards polygalacturonic acid as substrate as compared to pectin indicating a predominantly exoacting polygalacturonase of pectinase present. Cellulase enzyme activity was also detected. Optimum temperature and pH for crude pectinase enzyme activity was determined as 50°C and pH 4.0, respectively. Crude pectinase was also determined to be stable at temperature up to 37°C. It was found to be stable at pH ranging from pH 4.0 to pH 7.0. It was stable when stored at 4°C~ however the enzyme activity decreased to 40% after storage at 25°C for seven days. Partially purified pectinase enzyme was prepared using ammonium sulphate precipitation and enzyme characterization studies based on exo-polygalacturonase were also conducted. Dialyzed fraction of ammonium sulphate precipitation at 60% to 90% showed detectable exo-polygalacturonase activity. Partially purified pectinase also shows a higher affinity towards polygalacturonic acid. Kinetic parameters were determined with Km calculated as 2.642 mgmL-1 and Vmax at 9.434 UmL-I• Optimum temperature and pH was determined to be at 40°C and pH 9.0, respectively. These characteristics differ from crude enzyme. Partially purified enzyme also showed high activity at temperature ranging from 4°C and up to 60°C and pH ranging from pH 4.0 to 10.0 comparable with exopolygalacturonases from other sources. This enzyme did not required metal ions to express its activity and an inhibitory effect was observed with CaCh, ZnS04 and HgCh at high concentration. Trial enzymatic retting for white pepper production was conducted with crude pectinase enzyme preparation extracted from A. versicolor A6 on solid state fermentation system. Decortication of green matured pepper berries at 90% was achieved on day five at 28°C and the decortications results obtained are comparable with commercial enzyme (peelzym, Novozyme). Dried pepper berries samples were known as enzyme retted white pepper. Microbial specifications of the enzymatic retted berries met the standards set by International Pepper Community. Aerobic plate count was less than 250 CFUg-1, total colifonn count was 48 MPNg-1 with Escherichia coli detennined to be less than 3.0 MPNg-1• No Salmonella was detected in the enzyme retted pepper berries. Mold and yeast content was determined to be at 48 CFUg-1• Quality analysis regarding volatile oil, piperine, noovolatile ether extract, total ash and acid insoluble ash content was determined and met the standards set by International Pepper Community. Mycotoxins such as aflatoxin B" B2, 0 1 and 02 were not detected in all samples. Enzymatic retting with crude pectinase enzyme preparation has potential for further development and application as trial enzymatic retting yielded good quality end-products and reduced the time needed in production of white pepper compared to water retting method.